EDUKASI PENGGUNAAN AIR YANG TERKONTAMINASI BAKTERI Escherichia coli DAN coliform GUNA MENGURANGI KEJADIAN DIARE DI DISTRIK DEMTA KABUPATEN JAYAPURA TAHUN 2024 - Fajar Bakti Kurniawan; Risda Haratati; Meydi Johana Imbiri; Asrori; Rudolfo Tubalawony; Yulianus Wima Krisna Alfreda (Jurnal Masyarakat Indonesia (Jumas), 2024)
Clean water is water used for daily needs with quality that meets hygiene requirements. Poor environmental sanitation can increase the deposit of microorganisms in water. Water containing microorganisms can cause diarrhea. Diarrhea is still a health problem in Demta District, and one of the contributing factors is the consumption of water contaminated with Escherichia coli bacteria. Demta is a district in Jayapura Regency, which consists of several villages, including Kampung Ambora, Demda, Kamdera, Muaif, Muris Kecil, Yakore and Yaugapsa. Based on a survey in the Demta District, household activities, cooking, washing and drinking water come from mountain waterfalls which are channeled through pipes to homes. Based on the results of research on water samples in Demta District, Jayapura Regency in 2023, it was found that 5 samples did not meet the requirements (positive for bacteria Escherichia coli and coliforms). This community service aims to disseminate research results to the public in order to prevent the spread of diseases caused by bacteria Escherichia coli and coliforms. This community service was carried out for 6 months in Demta District, Jayapura Regency in June - November 2024. Activities carried out ranged from surveys, outreach and education on research results, handling water through boiling for the community before consumption.